2019
DOI: 10.1080/09638288.2019.1573932
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness of children and adolescents with moderate to severe intellectual disabilities

Abstract: Background: Low levels of physical fitness are associated with low physical and mental health. The aims of this study were to assess the health-related physical fitness of children with intellectual disability (ID), and study the association of physical activity and motor development with physical fitness. Methods: One hundred and twenty-eight children with moderate to severe ID (83 boys; age 2-18 years) visiting specialised day programme centres engaged in field-based physical fitness tests (body composition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 89 publications
(138 reference statements)
2
45
1
4
Order By: Relevance
“…Despite the fact that the individuals with intellectual disabilities who participated in the present study had some type of musculoskeletal and physical-sporting problem [57], it was possible to achieve improvements in general physical state, physical activity, as well as skills and motor skills [65]. Sessions lasting between 45 and 60 min produced improvements in the motor functioning of individuals with severe and profound intellectual disabilities [43]. Daytime specialist centers in Spain are not required to organize physical education sessions, in contrast to what occurs in the case of regular education, which is of course mandatory.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Despite the fact that the individuals with intellectual disabilities who participated in the present study had some type of musculoskeletal and physical-sporting problem [57], it was possible to achieve improvements in general physical state, physical activity, as well as skills and motor skills [65]. Sessions lasting between 45 and 60 min produced improvements in the motor functioning of individuals with severe and profound intellectual disabilities [43]. Daytime specialist centers in Spain are not required to organize physical education sessions, in contrast to what occurs in the case of regular education, which is of course mandatory.…”
Section: Discussionmentioning
confidence: 83%
“…The study was centered on health-related components of physical aptitude and followed the categories proposed by the American College of Sports Medicine (ACSM), i.e., body composition, muscular strength, and endurance [43]. Flexibility was not included in accordance with the recommendations proposed by Ganley et al [44].…”
Section: Variables and Instrumentsmentioning
confidence: 99%
“…The authors suggest that exergames can be also useful for children with impaired motor functions, for people who undergo rehabilitation, and for the elders [301]. Perhaps, the possibility to perform PA in the context of a virtual game can help also in the case of children and adolescents with intellectual disabilities (ID); it has been reported that children with moderate to severe ID also suffer from low physical fitness [302].…”
Section: Discussionmentioning
confidence: 99%
“…While the walking circuit was intentionally designed to ensure the selected skills could be completed independently by the participants, the intensity of skills was limited and focused on acquisition. Although there are known challenges, it is important for future research to continue to explore effective ways to engage participants with DD in PA that involve higher levels of intensity (Wouters et al, 2019a(Wouters et al, , 2019b. Participating in activities such as cardiovascular workouts focused on targeting certain heart rate zones are needed to help ensure individuals with DD are exposed to and will benefit from recommended levels of moderate to vigorous PA (Center for Disease Control [CDC], 2015).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%